Bunga Bank, Bagi Hasil dan Relijiusitas: suatu Investigasi Loyalitas Nasabah terhadap Perbankan Syari’ah - Munrokhim Misanam; Lili Liana (Universitas Islam Indonesia, 2007)
The recommendation of Indonesian Moslem Scholar Council (Majelis Ulama Indonesia, MUI) about the status of bank interest which is categorized a riba has been striking. The implied expectation was that there would be a massive fund migration from conventional banking into syari’ah one. The evidence, however, shows that this is not the case. The amount of deposit and other form of account in syari’ah banking increases only slightly. This evidence prompts a spe¬cu¬lation as to what has been the underlying cause behind the evidence. The main suspicion is that the degree of religiosity of depositing people has big energy to drive the emergence of the fact.The research aimed at getting the fix answer over this paradox issue. It explores the theoretical model centered on consumer and saving choice theory in addition to an investment theory, over which hypotheses are derived. It also employees systematic random sampling to get around three hundred fifty respondents scattered over three banks: Bank Syari’ah Mandiri, Bank Muammalah and Bank Rakyat Indonesia all are in YogyakartaApproaching the estimation with Logit type Dummy-dependent variable and Maximum likelihood estimation, it found that conventional bank interest, profit share and attribute of syari’ah banks are all significant event in less that one percent while the religiosity is insignificant, instead This findings are implicative in that syari’ah banking should also prospect the non-Moslem for their customer and sharpening the quality of their services.Keywords: interest, profit share, attribute, loyality